ARTIFICIAL INTELLIGENCE AND CUSTOMER EXPERIENCE: RELATIONSHIP TO NETFLIX CUSTOMER LOYALTY THROUGH CUSTOMER SATIFACTION - Ferdynand, Nicholas Ariesta; Saktiana, Galuh Mira (Graduate Program of Universitas Tarumanagara, 2025)
The development of technology is growing faster and more sophisticated. Competition among online streaming service providers in Indonesia is fierce. Netflix and similar companies are seeking methods to attract and retain loyal customers. This research seeks to uncover the relationships among several Netflix metrics, including artificial intelligence, customer experience, customer loyalty, and customer satisfaction. For this study, a cross-sectional descriptive quantitative method was applied. The analysis of the data was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the assistance of SmartPLS 4 software. A questionnaire is employed in this study's non-probability sampling with purposive sampling strategy, which collects data from up to 200 valid respondents. The study's findings reveal that Artificial Intelligence does not impact on Customer Loyalty. Conversely, both Customer Experience and Customer Satisfaction exert a positive and significant influence on Customer Loyalty. Additionally, Artificial Intelligence and Customer Experience positively and significantly affect Customer Satisfaction. Moreover, Customer Satisfaction mediates the indirect effects of Artificial Intelligence and Customer Experience on Customer Loyalty.